2024
DOI: 10.1186/s12913-023-10536-1
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to the implementation of digital technologies in mental health systems: a qualitative systematic review to inform a policy framework

Chiara Berardi,
Marcello Antonini,
Zephanie Jordan
et al.

Abstract: Background Despite the potential for improved population mental health and wellbeing, the integration of mental health digital interventions has been difficult to achieve. In this qualitative systematic review, we aimed to identify barriers and facilitators to the implementation of digital technologies in mental healthcare systems, and map these to an implementation framework to inform policy development. Methods We searched Medline, Embase, Scopus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 139 publications
(688 reference statements)
0
4
0
Order By: Relevance
“…According to the World Health Organization [36] digital innovation is happening at an unprecedented scale-not only in Eds-hereby harnessing the power of such technologies and health innovation to accelerate global attainment of health and wellbeing [36]. However, it seems like there is a need to increase ED nurses' knowledge about the effectiveness of such tools to achieve more positive attitudes and, therefore, acceptance [9][10][11][12]. Digital literacy has been defined as "the ability to access, manage, understand, integrate, communicate, evaluate and create information safely and appropriately through digital technologies for employment, decent jobs and entrepreneurship" [37].…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the World Health Organization [36] digital innovation is happening at an unprecedented scale-not only in Eds-hereby harnessing the power of such technologies and health innovation to accelerate global attainment of health and wellbeing [36]. However, it seems like there is a need to increase ED nurses' knowledge about the effectiveness of such tools to achieve more positive attitudes and, therefore, acceptance [9][10][11][12]. Digital literacy has been defined as "the ability to access, manage, understand, integrate, communicate, evaluate and create information safely and appropriately through digital technologies for employment, decent jobs and entrepreneurship" [37].…”
Section: Discussion Of Main Findingsmentioning
confidence: 99%
“…Studies show that healthcare personnel's knowledge impacts whether digital technology is adopted or not [9,10]. Also, their attitudes are important aspects in the acceptance and implementation of new technologies [11,12]. A study of urgent care clinicians' perceptions of digital access to patients' past medical history in the ED found that clinicians had a high level of technology acceptance, even if they also had several areas that needed improvement [13].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The main reasons include performance expectancy, effort expectancy, and facilitating conditions, which act as significant determinants to users' behavioral intention. Others have drawn on regulatory, compliance, and legal challenges that the digital health revolution is creating for the healthcare sector: 7 the skepticism about the effectiveness of the technology 8 and the quality of the services provided and the vulnerability of technology to risks such as cyberattacks 9 to report a few. Not surprisingly, often decidedly nontechnological barriers are identified as major barriers to digital transformation.…”
Section: Digital Transformation In Industry: An Exemplar For Health C...mentioning
confidence: 99%
“…The progressive computerization of our clinical records and the introduction of novel technology in the assistance of our patients, for example, are tangible realities. Although these changes in our clinical practice can undoubtedly be beneficial, they often constitute a challenge and require further research to optimize them[ 1 ].…”
Section: Introductionmentioning
confidence: 99%